Chloroquine as weekly chemoprophylaxis or intermittent treatment to prevent malaria in pregnancy in Malawi: a randomised controlled trial. Issue 10 (October 2018) - Divala, Titus H; Mungwira, Randy G; Mawindo, Patricia M; Nyirenda, Osward M; Kanjala, Maxwell; Ndaferankhande, Masiye; Tsirizani, Lufina E; Masonga, Rhoda; Muwalo, Francis; Boudová, Sarah; Potter, Gail E; Kennedy, Jessie; et al.
Summary: Background: Sulfadoxine-pyrimethamine resistance threatens efficacy of intermittent preventive treatment of malaria during pregnancy, and alternative regimens need to be identified. With the return of chloroquine efficacy in southern Africa, we postulated that chloroquine either as an intermittent therapy or as weekly chemoprophylaxis would be more efficacious than intermittent sulfadoxine-pyrimethamine for prevention of malaria in pregnancy and associated maternal and newborn adverse outcomes. Methods: We did an open-label, single-centre, randomised controlled trial at Ndirande Health Centre, Blantyre, in southern Malawi. We enrolled pregnant women (first or second pregnancy) at 20–28 weeks' gestation who were HIV negative. Participants were randomly assigned in a 1:1:1 ratio using a computer-generated list to either intermittent sulfadoxine-pyrimethamine (two doses of 1500 mg sulfadoxine and 75 mg pyrimethamine, 4 weeks apart), intermittent chloroquine (two doses of 600 mg on day 1, 600 mg on day 2, and 300 mg on day 3), or chloroquine prophylaxis (600 mg on day 1 then 300 mg every week). The primary endpoint was placental malaria in the modified intent-to-treat population, which consisted of participants who contributed placental histopathology data at birth. Secondary outcomes included clinical malaria, maternal anaemia, low birthweight, and safety. This trial is registered withClinicalTrials.gov, numberNCT01443130 . Findings: Between February, 2012, and May, 2014, we enrolled and randomly allocated 900 women, of whom 765 contributed histopathological data and were included in the primary analysis. 108 (14%) women had placental malaria, which was lower than the anticipated prevalence of placental malaria infection. Protection from placental malaria was not improved by chloroquine as either prophylaxis (30 [12%] of 259 had positive histopathology; relative risk [RR] 0·75, 95% CI 0·48–1·17) or intermittent therapy (39 [15%] of 253; RR 1·00, 0·67–1·50) compared with intermittent sulfadoxine-pyrimethamine (39 [15%] of 253). In protocol-specified analyses adjusted for maternal age, gestational age at enrolment, bednet use the night before enrolment, anaemia at enrolment, and malaria infection at enrolment, women taking chloroquine as prophylaxis had 34% lower placental infections than did those allocated intermittent sulfadoxine-pyrimethamine (RR 0·66, 95% CI 0·46–0·95). Clinical malaria was reported in nine women assigned intermittent sulfadoxine-pyrimethamine, four allocated intermittent chloroquine (p=0·26), and two allocated chloroquine prophylaxis (p=0·063). Maternal anaemia was noted in five women assigned intermittent sulfadoxine-pyrimethamine, 15 allocated intermittent chloroquine (p=0·038), and six assigned chloroquine prophylaxis (p>0·99). Low birthweight was recorded for 31 babies born to women allocated intermittent sulfadoxine-pyrimethamine, 29 assigned intermittent chloroquine (p=0·78), and 41 allocated chloroquine prophylaxis (p=0·28). Four women assigned intermittent sulfadoxine-pyrimethamine had adverse events possibly related to study product compared with 94 women allocated intermittent chloroquine (p<0·0001) and 26 allocated chloroquine prophylaxis (p<0·0001). Three women had severe or life-threatening adverse events related to study product, of whom all were assigned intermittent chloroquine (p=0·25). Interpretation: Chloroquine administered as intermittent therapy did not provide better protection from malaria and related adverse effects compared with intermittent sulfadoxine-pyrimethamine in a setting of high resistance to sulfadoxine-pyrimethamine. Chloroquine chemoprophylaxis might provide benefit in protecting against malaria during pregnancy, but studies with larger sample sizes are needed to confirm these results. Funding: US National Institutes of Health.